2007
DOI: 10.1111/j.1744-7402.2007.02132.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Temperature Reversible Fuel Cells

Abstract: Electrolysis of water produces high‐purity hydrogen directly, with no need for additional clean‐up process. Efficiency and cost of electrolysis are favorable with high‐temperature steam electrolyzers where a portion of the required energy can be supplied as thermal energy. With the similarity in requirements, much of the materials and designs aspects for the high‐temperature electrolyzers have been derived from solid oxide fuel cell development. Lanthanum gallate electrolyte‐based cells were evaluated in fuel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…SOEC, a reverse mode of SOFC, produces hydrogen by splitting water steam into hydrogen and oxygen at high temperatures. Thus SOCs have the potential to produce clean energy or clean synthetic fuel 1 . The planar mode of SOCs is more attractive because of its higher power density, lower cost, and relative ease of fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…SOEC, a reverse mode of SOFC, produces hydrogen by splitting water steam into hydrogen and oxygen at high temperatures. Thus SOCs have the potential to produce clean energy or clean synthetic fuel 1 . The planar mode of SOCs is more attractive because of its higher power density, lower cost, and relative ease of fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…The necessity to store energy from the increasing amounts of electricity from renewable energy sources has renewed the interest for using SOCs for electrolysis purposes, and recently several research groups have reported on SOEC R&D work. [6][7][8][9][10][11][12][13][14][15][16] From a fundamental thermodynamic and electrochemical point of view it is clear that high temperature electrolysis of steam can provide H 2 with high efficiency and high purity, and SOECs can be used as buffers to optimize the efficiency of intermittent sources, such as wind power, and utilize waste heat and surplus energy from, e.g., nuclear power facilities during off-peak hours. However, for these cells to become successful from a technological and commercial point of view for H 2 and synthetic fuel production, SOECs need to be cost competitive, high performing, and long-term stable.…”
mentioning
confidence: 99%
“…Current density variations for the same electrode material systems are due to starting material characteristics, processing, electrode microstructure, absolute humidity input, and flow rates. Figure 16.19 graphically shows data reported in the literature for current densities at V tn between 500 and 900°C along with the range of values for various types of SOEC [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. The performance of SOEC single cells, like SOFCs, can be improved by using nanoparticles to modify electrode microstructures [61,62].…”
Section: Solid Oxide Electrolysis Cell Technologymentioning
confidence: 99%
“…19 Current densities at thermoneutral voltage reported for various types of SOEC between 500 and 900°C (the bars show the range of values)[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
mentioning
confidence: 99%